The geography class: some writings - Silva, Luan do Carmo da (Revista Ensino de Geografia (Recife), 2022)
The main objective of the text is to discuss the weaknesses and inflections of the process of initial teacher training evidenced during the activities related to the process of planning and conducting classes in the curricular components of Supervised Internship and Teaching Practices, of the Geography course offered by the Federal Institute of Education, Science and Technology of Brasília (IFB) between the years 2020 and 2021. All discussions were based on the list of expectations of the undergraduates and point to different conceptions of Geography, being a teacher and the teaching-learning process that students carry with them.